The Effect Of Gadgets On The Development Of Youth In Genteng Banyuwangi - Harwanti Noviandari; Agus Mursidi; Eko Listiwikono (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
Teenagers are facilitated in accessing the world of information and have a lot of influence on human life and child development. The use of gadgets has a positive impact on human life, but if used excessively it will have a negative impact, especially for children. The positive impact of using gadgets for children, including in the mindset of children, namely: being able to help children in regulating the speed of their play, processing strategies in games, and helping to improve the ability of the child's right brain while under good supervision. On the other hand, the negative impacts of using gadgets for children include: children become difficult to socialize, unstable in emotional control, slow in motor development, the emergence of a sense of laziness, waste, significant behavioral changes to changes in academic achievement at school.The target audience of this service activity are PKK Korsda women at the Banyuwangi Tile Irrigation Service. The women of PKK Korsda of the Banyuwangi Tile Irrigation Service became the target audience because there was a request from the head of the PKK Korsda of the Banyuwangi Irrigation Service at the Banyuwangi PGRI University who needed resource persons in the activities of the PKK Korsda women of the Tile Irrigation Service. The activity is carried out every month, so that the service activities carried out by the PGRI Banyuwangi University service team are adjusted to the needs.